Heat transfer in thermoanemometric biofuels flowmeter - Ільченко, Андрій Володимирович; Безвесільна, Олена Миколаївна; Тростенюк, Юрій Волерійьович (Eastern-European Journal of Enterprise Technologies, 2014)
The article introduces the equations which reflect variations of the thermal conductivity coefficient of a mixture of petroleum-based fuels, depending on the volume percent concentration of ethanol, and variations of the thermal conductivity coefficient of mixtures of fuels with diesel fuel as a basis, depending on the volume percent concentration of the vegetable oil. It is shown that the fuel temperature at the level of its consumption ranging from 0 to 25 l/h at a distance from 1 to 6 cm from the heater of a flowmeter can be represented by a straight line approximation. Analyzed are radial and axial heat flows in the tube of a termoanemometric flowmeter taking into consideration the influence of the thermal conductivity of biological components of the fuel, their concentration in the fuel mixture. The proposed equations allow us to determine the temperature of the fuel stream and the consumption rate of a car. It is proven the numerical value of the termoanemometric flowmeter tube structural coefficient, which under the condition of reducing the measurement error of fuel consumption must be equal to 15,5. It is proven that the thermal conductivity of the material of a flowmeter tube has little effect on heat flux.